Mercerization effect on the properties of LDPE/PHB composites reinforced with castor cake - Rocha,Marisa Cristina Guimarães (2020)
Abstract The aim of this work was to investigate the effects of mercerization on the structure of castor oil cake (CC) and on the tensile properties of LDPE/PHB/CC composites. To achieve this goal, the fibers were treated with NaOH solutions (5 and 10 wt%). Characterization techniques such as: scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) were used to investigate the structure of modified fibers. The composites were processed in a Haake mixer. Tensile tests of the composites were performed according to ASTM D638 standard. The analyzes revealed that mercerization promoted a partial conversion of cellulose I into cellulose II. Mercerization performed with 5% NaOH solution improved the tensile properties of the LDPE/PHB/CC composites, which were superior to those obtained with the 10% NaOH solution. This result suggests that the higher concentration of NaOH compromises the integrity of the fibers, deteriorating the mechanical properties.